(3aQjb GdYeds - (3RjO efjQ(B, (3YHhjs; (3jhSa PjH GdYWGQj(B, s ((3YeGJ(B:s (3OGQ GdNdjL(B,s, 2012)
(3Gdgjcd h Sdhc GdeLehYGJ , JCKjQ GdeLehYGJ Ydi eOi JMbjb GdGaOGa dJhbYGJge , GJNGP GdbQGQGJ GdLeGYjI h bjGS GdYed GdLeGYj h Jbhje GdCOGA GdeDSSj , GdhdGA aj GdYed GdLeGYj , GdegGQGJ GdGfJGLjI aj GdYed GdLeGYj , GdYhGed GdJj JSGYO Ydi fLGM GdJMOjK aj GdYed GdLeGYj , GdaQb h aQb GdYed , OjfGejGJ GdYed GdLeGYj h egGQI HfGA GdaQjb (B.s
Keywords: (3GJNGP GdbQGQGJs; (3GdEOGQIs; (3GdYed GdLeGYjs